The risk of dementia after coronary artery bypass grafting in relation to age and sex - Giang, Kok Wai; Jeppsson, Anders; Karlsson, Martin; Hansson, Emma C.; Pivodic, Aldina; Skoog, Ingmar; Lindgren, Martin; Nielsen, Susanne J. (Alzheimer's & dementia, 2021)
Introduction We examined the long‐term risk of dementia after coronary artery bypass grafting (CABG) in relation to age and sex. Methods All CABG patients in Sweden 1992–2015 (n = 111,335), and matched controls (n = 222,396) were included in a population‐based study. Adjusted hazard ratios (aHR) for all‐cause dementia, vascular dementia, and Alzheimer's disease were calculated. Results There was no difference in the risk for all‐cause dementia between CABG patients and control subjects (aHR 0.98 [95% confidence interval 0.95 to 1.02]). CABG patients <65 years and 65 to 74 years had higher risk (aHR 1.29 [1.17–1.42] and 1.08 [1.02–1.13], respectively), and patients ≥75 years had lower risk (aHR 0.76 [0.71–0.81]). The highest risk was observed in women <65 years (aHR 1.64 [1.31–2.05]). Discussion Overall, the long‐term risk for all‐cause dementia does not differ between CABG patients and the general population. Younger patients have a higher risk, while older patients have a lower risk, compared to controls.